Pengaruh Bahasa Ibu Pada Perilaku Anak (Kajian dari sudut pandang cara kerja pikiran) - Salami, Salami (Universitas Islam Negeri Ar-Raniry, 2016)
The mother is madrasah Å«lÄ for her childrenâ€™s growth and development. The interaction between the mother and the son or the daughter starts since the child is still in her uterus. So, whatever the mother feels, thinks, and says, positively or negatively, will impact directly to the childâ€™s behaviour. The research is developing on the influence of the languageused by the mother to the growth and development of the child, especially psychological development. This condition will inpact to his or her behaviour in the future. So, the mother has to learn continously some knowledges that relate to educating children until she can give positive influence and avoid negative one to their development. Because the mother is able to influence her childrenâ€™s behaviour in different interactions verbal or gestural, she has to pay a lot of attention to the language patterns that she used in communicating with her children.